Penerapan Evidence Based Practice Efektivitas Health Education dalam Self Care pada Pasien dengan Heart Failure di RSPAD Gatot Soebroto Jakarta - Mulyadi, Egi; Jumaiyah, Wati; Yunitri, Ninik (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Heart failure has a variety of terms including right, left, combined and congestive heart failure. Left heart failure is characterized by fluid buildup in the lungs, low blood pressure, and constriction of peripheral blood vessels which results in reduced blood flow to the tissues. Right heart failure is characterized by edema in the opposite side of the body, fluid in the abdominal cavity, and increased pressure in the main blood vessels leading to the heart. Congestive heart failure is a combination of symptoms of both types of heart failure. Even though outpatient treatment is optimal, heart failure often requires intensive hospital treatment. To find the level of success of health education in caring for patients with heart failure. Data analysis in this paper applies univariate data analysis to observe demographic characteristics and changes in the level of awareness of each respondent. Next, statistical tests were used with the paired t-test to evaluate the effect of awareness level before and after implementing Familiar Auditory Sensory Training, with a significance level of 0.05. The author counted the number of respondents using G*Power Version 3.1 software (Kang, 2021) with a total of 11 respondents. Data analysis in this paper uses univariate data analysis to evaluate the demographic characteristics and self-care description of each respondent. Furthermore, if the data has a normal distribution, the self-care statistical test uses the paired t-test, whereas if the data does not have a normal distribution, the self-care statistical test uses the Mann Whitney U test to evaluate self-care behavior after health education. Respondents had an average age of over 56.3 years, with the majority being male (75%) and the majority having secondary school level education (81.3%). They had suffered from heart failure on average for 4.31 years, and the majority were classified as classification II (62.5%). Before the intervention, the frequency of Self Care Behavior was 22.3 (standard deviation 4.58), which increased to 27.1 after the intervention (standard deviation 7.34). The normality test shows normal data distribution (p-value 0.968), and the dependent t-test analysis shows significant differences before and after the intervention (p-value 0.011 < 0.05), indicating the positive impact of health education on self-care in patients with heart failure. Keywords: Evidence Based Practice, Health Education, Self Care, Heart FailureABSTRAK Gagal jantung memiliki variasi istilah yang meliputi gagal jantung kanan, kiri, kombinasi, dan kongestif. Gagal jantung kiri dicirikan oleh adanya penumpukan cairan di paru-paru, tekanan darah rendah, dan konstriksi pembuluh darah perifer yang mengakibatkan berkurangnya aliran darah ke jaringan. Gagal jantung kanan ditandai dengan edema di bagian tubuh yang berlawanan, cairan di rongga perut, dan peningkatan tekanan di pembuluh darah utama yang mengarah ke jantung. Gagal jantung kongestif merupakan kombinasi dari gejala kedua jenis gagal jantung tersebut. Meskipun pengobatan rawat jalan telah diberikan dengan optimal, penyakit gagal jantung sering kali membutuhkan perawatan di rumah sakit yang intensif. Menemukan tingkat keberhasilan pendidikan kesehatan dalam merawat diri pada pasien dengan gagal jantung.  Analisis data dalam penulisan ini menggunakan analisis data univariat untuk mengevaluasi karakteristik demografi dan gambaran self care pada setiap responden. Selanjutnya, jika data memiliki distribusi normal, uji statistik self care menggunakan uji paired t-Test, sedangkan jika data tidak memiliki distribusi normal, uji statistik self care menggunakan uji Mann Whitney U untuk mengevaluasi self care behavior setelah dilakukan pendidikan kesehatan. Responden memiliki usia rata-rata di atas 56,3 tahun, dengan mayoritas berjenis kelamin laki-laki (75%) dan mayoritas memiliki pendidikan tingkat sekolah menengah (81,3%). Mereka rata-rata telah menderita penyakit gagal jantung selama 4,31 tahun, dan mayoritas termasuk dalam klasifikasi II (62,5%). Sebelum intervensi, frekuensi Self Care Behaviour adalah 22,3 (deviasi standar 4,58), yang meningkat menjadi 27,1 setelah intervensi (deviasi standar 7,34). Uji normalitas menunjukkan distribusi data yang normal (p-value 0,968), dan analisis dependent t-Test menunjukkan perbedaan yang signifikan sebelum dan sesudah intervensi (p-value 0,011 < 0,05), menunjukkan dampak positif health education terhadap self care pada pasien dengan gagal jantung. Kata Kunci: Praktek Berbasis Bukti, Pendidikan Kesehatan, Perawatan Diri, Gagal Jantung